Setting up a cohort study in speech and language therapy: lessons from The UK Cleft Collective Speech and Language (CC‐SL) study. Issue 3 (18th December 2017) - Wren, Yvonne; Humphries, Kerry; Stock, Nicola Marie; Rumsey, Nichola; Lewis, Sarah; Davies, Amy; Bennett, Rhiannon; Sandy, Jonathan
Abstract: Background: Efforts to increase the evidence base in speech and language therapy are often limited by methodological factors that have restricted the strength of the evidence to the lower levels of the evidence hierarchy. Where higher graded studies, such as randomized controlled trials, have been carried out, it has sometimes been difficult to obtain sufficient power to detect a potential effect of intervention owing to small sample sizes or heterogeneity in the participants. With certain clinical groups such as cleft lip and palate, systematic reviews of intervention studies have shown that there is no robust evidence to support the efficacy of any one intervention protocol over another. Aims: To describe the setting up of an observational clinical cohort study and to present this as an alternative design for answering research questions relating to prevalence, risk factors and outcomes from intervention. Methods: The Cleft Collective Speech and Language (CC‐SL) study is a national cohort study of children born with cleft palate. Working in partnership with regional clinical cleft centres, a sample size of over 600 children and 600 parents is being recruited and followed up from birth to age 5 years. Variables being collected include demographic, psychological, surgical, hearing, and speech and language data. Main Contribution: The process of setting up the study has led to the creation of a unique, large‐scale data set which is available for researchers to access now and in future. As well as exploring predictive factors, the data can be used to explore the impact of interventions in relation to individual differences. Findings from these investigations can be used to provide information on sample criteria and definitions of intervention and dosage which can be used in future trials. Conclusions: The observational cohort study is a useful alternative design to explore questions around prevalence, risk factors and intervention for clinical groups where robust research data are not yet available. Findings from such a study can be used to guide service‐delivery decisions and to determine power for future clinical trials.